THE TEACHING OF ISLAMIC EDUCATION IN THE MULTICULTURAL SCHOOL ENVIRONMENT: APPROACHES AND CHALLENGES - Fuadi, Nazid Zaki; Shohib, Muhammad Wildan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This study aims to analyze the implementation of multicultural Islamic education, identify the challenges faced in teaching multicultural Islamic education, and understand teachers' strategies to overcome these challenges. This study reveals that implementing multicultural Islamic education involves the integration of religious values with a deep understanding of culture and diversity. The main challenges include traditional performance, a lack of human resources who understand this concept, socio-cultural opposition, political aspects, globalization, radicalism, and differences in views about religion and the state. Teachers have a significant role in overcoming this challenge by providing learning materials that positively reflect group differences, using multicultural textbooks, and implementing cooperative learning strategies. In addition, teachers need flexibility in adapting learning methods according to students' abilities and instilling multicultural values. The application of multicultural Islamic education has great potential for creating an inclusive, harmonious learning environment and reducing prejudice and discrimination to achieve a more inclusive society and respect for diversity.